2021
DOI: 10.3390/molecules26195946
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Active Ingredients Targeted TREM2 by SPR Biosensor-UPLC/MS Recognition System, and Investigating the Mechanism of Anti-Neuroinflammatory Activity on the Lignin-Amides from Datura metel Seeds

Abstract: As a new target protein for Alzheimer’s disease (AD), the triggering receptor expressed on myeloid Cells 2 (TREM2) was expressed on the surface of microglia, which was shown to regulate neuroinflammation, be associated with a variety of neuropathologic, and regarded as a potential indicator for monitoring AD. In this study, a novel recognition system based on surface plasmon resonance (SPR) for the TREM2 target spot was established coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-MS), in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… Anti-cancer activity Maehara et al, 2020 Baimantuoluoline A Flower 50% Ethanol Showed the activity for psoriasis Yang et al, 2007 (5α,6β,7α,22R)-5,6,7,27- tetrahydroxy-1-oxowitha- 2,24-dien-27-O-β-D- glucopyranoside Flower Extracted with 70% Ethanol For treating of psoriasis Yang et al (2010b) 6,7-dimethyl-1-D-ribityl-quinoxaline-2,3(1H,4H) - dione-5′-O-β- Dglucopyranoside Flower Used 70% Ethanol Psoriasis treatment Yang et al (2010b) Sesquiterpenoid and aliphatic glycoside Roots 70% Ethanol Anti-inflammatory activity by 5 compounds Liu et al, 2022 (E)-methyl 4-(3-(4hydroxyphenyl) -N- methylacrylamido) butanoate Flower 70% Ethanol used for extraction Treatment of psoriasis Yang et al, 2010a Ergostane-type C28 sterols, daturmetesides A-E (1–5) Leaves 70% Ethanol Anti-inflammatory activity, IC 50 values ranging from 17.05 ± 0.35 μM to 24.88 ± 0.93. Tan et al, 2020b 1, 10-seco-withametelin B Flower Methanolic extraction Cytotoxicity is observed Pan et al, 2007 12 β -hydroxy-1,10-seco- withametelin B Flower Methanolic extraction Cytotoxicity is observed Pan et al, 2007 Alkaloid datumetine Leaves Para-methoxy benzoic acid Anti-spasmodic action Siddiqui et al, 1987 Lignin-amides from Datura metel seeds (LDS) Seeds 95% Ethanol Anti-neuroinflammatory, Alzheimer disorder Wang et al, 2021 2-(3,4-dimethyl-2,5-dihydro-1H-pyrrol-2-...…”
Section: Resultsmentioning
confidence: 99%
“… Anti-cancer activity Maehara et al, 2020 Baimantuoluoline A Flower 50% Ethanol Showed the activity for psoriasis Yang et al, 2007 (5α,6β,7α,22R)-5,6,7,27- tetrahydroxy-1-oxowitha- 2,24-dien-27-O-β-D- glucopyranoside Flower Extracted with 70% Ethanol For treating of psoriasis Yang et al (2010b) 6,7-dimethyl-1-D-ribityl-quinoxaline-2,3(1H,4H) - dione-5′-O-β- Dglucopyranoside Flower Used 70% Ethanol Psoriasis treatment Yang et al (2010b) Sesquiterpenoid and aliphatic glycoside Roots 70% Ethanol Anti-inflammatory activity by 5 compounds Liu et al, 2022 (E)-methyl 4-(3-(4hydroxyphenyl) -N- methylacrylamido) butanoate Flower 70% Ethanol used for extraction Treatment of psoriasis Yang et al, 2010a Ergostane-type C28 sterols, daturmetesides A-E (1–5) Leaves 70% Ethanol Anti-inflammatory activity, IC 50 values ranging from 17.05 ± 0.35 μM to 24.88 ± 0.93. Tan et al, 2020b 1, 10-seco-withametelin B Flower Methanolic extraction Cytotoxicity is observed Pan et al, 2007 12 β -hydroxy-1,10-seco- withametelin B Flower Methanolic extraction Cytotoxicity is observed Pan et al, 2007 Alkaloid datumetine Leaves Para-methoxy benzoic acid Anti-spasmodic action Siddiqui et al, 1987 Lignin-amides from Datura metel seeds (LDS) Seeds 95% Ethanol Anti-neuroinflammatory, Alzheimer disorder Wang et al, 2021 2-(3,4-dimethyl-2,5-dihydro-1H-pyrrol-2-...…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pterostilbene, LDS is also able to ameliorate neuroinflammation through the NLRP3/caspase-1 pathway. Wang et al ( 217 ) found that LDS had anti-inflammatory activity in LPS-induced BV2 cells. Additionally, PPSR (PEG-PEI/siROCK2), a synthetic molecule used in gene therapy for AD, was found to inhibit the increase in IL-1β induced by LPS/Aβ in primary microglia through the NLRP3/caspase-1 pathway, thus exhibiting anti-inflammatory effects ( 218 ).…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…However, the CSF sampling route is difficult, expensive, and invasive, making it inconvenient for largescale or repetitive sampling in a long-time following disease progression or treatment efficacy. Human Tau protein is a promising serum biomarker for AD-that has gained significant attention for early and accurate molecular diagnostics [4][5][6][7]. However, the serum concentrations of Tau protein biomarkers are at the pg/mL level, and ultrahigh-sensitivity detection methods are in great demand for clinical applications.…”
Section: Introductionmentioning
confidence: 99%